2019
DOI: 10.1021/acs.orglett.8b04064
|View full text |Cite
|
Sign up to set email alerts
|

π-Extended Phosphepines: Redox and Optically Active P-Heterocycles with Nonplanar Framework

Abstract: In this letter, we present the synthesis of a new family of -extended dithieno[b,f]phosphepines. The Pd-catalyzed direct-arylation allows the introduction of various substituents, which tune the absorption/emission in the visible range as well as the redox properties. All those modifications were rationalized through DFT calculations. The physical properties of ambipolar phosphepine with diphenylamino substituents conduct us to use it as a semiconductor in a p-type organic field-effect transistors (OFETs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 22 publications
3
40
0
2
Order By: Relevance
“…DTP oxide 5β adopts a different conformation than the other DTPs with its oxygen atom being oriented almost perpendicular to the DTP backbone ( anti conformation). These features agree with those of the crystal structure reported for the same compound by Delouche et al . In contrast, the lone pairs, borane units, and oxo groups, respectively, are pointing in the same spatial direction as the thiophenes ( syn conformation) in case of all other derivatives.…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…DTP oxide 5β adopts a different conformation than the other DTPs with its oxygen atom being oriented almost perpendicular to the DTP backbone ( anti conformation). These features agree with those of the crystal structure reported for the same compound by Delouche et al . In contrast, the lone pairs, borane units, and oxo groups, respectively, are pointing in the same spatial direction as the thiophenes ( syn conformation) in case of all other derivatives.…”
Section: Methodssupporting
confidence: 91%
“…Very recently, Delouche et al. reported on the direct Pd‐catalyzed arylation of 5β , however, we found that this approach is not applicable to the corresponding α‐isomer. Instead, we were able to introduce phenylethynyl units through direct C−H functionalization of thiophene.…”
Section: Methodsmentioning
confidence: 67%
See 3 more Smart Citations